Intake and food sources of sodium in the population residing in urban areas of Ecuador: results from ELANS study - Villar Cáceres, Mónica (2023)
Background In 2021, WHO notes that globally, 32% of annual deaths worldwide are due to cardiovascular causes, which have been attributed to excessive sodium intake, and therefore recommends a reduction in salt intake to less than 5 g/day. Ecuador does not have data on sodium consumption in the population. Hence, this study sought to determine the association between sodium consumption and sociodemographic variables in subjects living in urban areas of Ecuador. Objectives Determine the main dietary sources of sodium in subjects living in urban areas of the Coast and Highlands of Ecuador, and the association between sodium intake and sociodemographic variables such as: sex, region, marital status, socio-economic and educational level of this population. Methods Sodium intake was studied in 800 subjects of both sexes aged 15 to 65 years living in urban areas in Ecuador, originating from the Latin American Nutrition and Health Study (ELANS) between 2014 and 2015. Data were obtained through two 24-hour recalls, and were accessed according to sex, region, age, marital status, socio-economic and educational levels. Results The mean sodium intake was 4900 mg/day (SD ± 1188.32 mg/day), and both sexes exceeded the recommendations. Adjusting for energy intake, sodium consumption is higher in participants aged 50–65 years, from low socio-economic status and with basic education level. A positive relationship was found between sodium and energy intake. Around 48% of the sodium sources included the spices, condiments and herbs group. Within this group, salt itself constitutes 99% of sodium sources. Conclusions The Ecuadorian population consumes more than double the sodium recommendations, which vary according to gender and age. The first source of sodium is salt itself, which is part of spices and condiments food group. This data is important to formulate public health policies and interventions in Ecuador, especially in the population at risk.